Anisotropic electrokinetic transport in channels modified with patterned polymer brushes. Issue 20 (2nd May 2019) - Cao, Qianqian
Abstract : Molecular dynamics simulations have been used to predict the transport dynamics of fluids through nanochannels with polymer patterning surfaces. Abstract : Molecular dynamics simulations have been used to predict the transport dynamics of fluids through nanochannels with polymer patterning surfaces. The effects of different parameters, such as separation between polymer stripes, solvent quality, and direction and strength of the electric field, were explored in terms of electroosmotic flow transport characteristics, conformational dynamics of the polymer brush and ion distribution. Anisotropic electrokinetic transport becomes significant due to the surface patterning of polymers when the direction of the electric field is changed. At the separation between adjacent polymer stripes comparable to the chain length, local strong flow close to the bare surfaces weakens dramatically under the electric field along the stripe direction. However, when the electric field is switched to the direction perpendicular to the stripes, the flow is enhanced considerably. The coupling of the polymer solvent quality further richens and complicates the transport behaviors. We explain the physical mechanism of the electroosmotic flow in complex polymer patterning channels by analyzing the interrelationship among various properties.